Migrants, the EU and NGOs: The ‘Practice’ of Non-Governmental SAR Operations - Daniela Irrera (Romanian Journal of European Affairs)
Migration issues are dominating current debates at all levels. The perception of migrants as a threat quite often prevails over the human dimension and is associated to the immediate emergency management phase, particularly in respect of recent developments in the Mediterranean. The analysis of the roles of NGOs, a combination of traditional assistance to development and social integration and more active interventions i.e. Search and rescue operation in the Mediterranean may offer some interesting insights. The paper is a preliminary analysis of such trends, and is enriched by the results of an expert survey research on the performance of Mare Nostrum and its capacity to manage the crisis. There are three major considerations consisting in an assessment of the literature on the role played by NGOs in EU migration policies, an analysis of the use of SAR by different actors, including the non-governmental, in order to investigate the impact on the management of the crisis and finally empirical data which are used to assess current trends and raise future perspectives.